Improving Accounting in Monopoly Organizations - Zurapov Ali Utkirovich (Genius Journals, 2022)
Based on the analysis of foreign and native scientific researches, the author developed proposals and recommendations on the theoretical and methodological foundations of the calculation of financial results in monopoly enterprises, determining the content and place of monopoly in society in the conditions of market relations, the share of monopoly in GDP, its positive aspects and theoretical and methodological foundations of the calculation.
Keywords: monopoly; standards; competitive; monopoly enterprise